2012
DOI: 10.1590/s0102-64452012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Raça e comportamento político: participação, ativismo e recursos em Belo Horizonte

Abstract: A discussão sobre raça na política brasileira é mote entre cientistas sociais de diversas perspectivas: pelo seu papel na formação do Estado nacional, nos movimentos sociais ou ainda nas políticas públicas voltadas a grupos raciais. Mas, pela maior parte da ciência política brasileira, é rapidamente descartada como irrelevante ou residual. Este texto, no entanto, toma o lugar da raça na política como uma questão central e propõe as seguintes questões: Qual é o papel da raça no comportamento político dos indiví… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(14 reference statements)
0
3
0
1
Order By: Relevance
“…This finding suggests that ethnicity might not substantially affect the propensity to act politically. In Brazil, socioeconomic factors, such as income and schooling, are clearly more relevant in boosting this type of participation than the direct effect of ethnicity 21 . So much so that higher schooling and income strata were more active in the social dimension, corroborating other studies 4, 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that ethnicity might not substantially affect the propensity to act politically. In Brazil, socioeconomic factors, such as income and schooling, are clearly more relevant in boosting this type of participation than the direct effect of ethnicity 21 . So much so that higher schooling and income strata were more active in the social dimension, corroborating other studies 4, 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, para analizar la participación política se debe considerar variables sociodemográficas, ya que denotan posición social, dotación de recursos, nivel de estudios alcanzado, los ingresos adquiridos, entre otros (Bueno 2012;Camacho, 2010, Anduiza y Agustí, 2004. Por eso se realizó un análisis sociodemográfico, los resultados del estudio evidenciaron una relación entre la condición social y la participación, pero no entre género y participación política, ya que los hombres obtuvieron casi los mismos niveles de participación que las mujeres.…”
Section: Consideraciones Finalesunclassified
“…Although this research has pointed out that even though race identification might lead to differential vote choice in the country despite the absence of a strong racial consciousness among non-Whites in Brazil (Souza, 1971; Soares and Valle Silva, 1985, 1987; Castro, 1993; de Souza Carreirão, 2007; Bailey, 2009; Mitchell, 2009; Peixoto and Rennó, 2011), its effect would not be a major determinant of voting behavior (Prandi, 1996; Rennó, 2007). Recent research on non-electoral political participation has also suggested that the major cause of unequal levels of participation between Whites and non-Whites is group differences in resource levels, since the effect of race on participation dissipates after controlling for resources (Bueno and Fialho, 2009; Bueno, 2012).…”
Section: Race and Participationmentioning
confidence: 99%